2021
DOI: 10.1111/chso.12480
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the moral experiences of Anishinaabeg children in Rapid Lake, Quebec

Abstract: This study was developed to guard against the imposition of settler‐based colonial ethnocentric conceptions of moral development by exploring the everyday moral experiences of children in an Anishinaabeg community. A focused ethnography of 33 children over 3.5 months was conducted, which included participant observation, group activities and individual and group interviews. Drawing on their unique cultural and social background, children showed they had rich moral understandings and acted as moral agents in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Although academic debate has highlighted gender inequalities in adult caring, little attention has been given to gendered care inequities among siblings (Boyle, 2020). However, research into how children and young people develop values and demonstrate moral agency has shown that they regard equality as a moral good and seek to address inequality (George et al, 2021). Nonetheless, gender equality concerns in youth research have primarily focused on educational attainment (for example, Commonwealth Education Hub, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Although academic debate has highlighted gender inequalities in adult caring, little attention has been given to gendered care inequities among siblings (Boyle, 2020). However, research into how children and young people develop values and demonstrate moral agency has shown that they regard equality as a moral good and seek to address inequality (George et al, 2021). Nonetheless, gender equality concerns in youth research have primarily focused on educational attainment (for example, Commonwealth Education Hub, 2016).…”
Section: Resultsmentioning
confidence: 99%